PERAN KARAKTERISTIK KERJA DAN LINGKUNGAN KINERJA KARYAWAN PT. BANK MANDIRI CABANG TANJUNG MORAWA - Wardoyo, Arief Alfaresyi (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2025)
The purpose of this research is to investigate and analyze the role of work characteristics and environment on employee performance at PT. Bank Mandiri, Tanjung Morawa. This type of research is descriptive research. The technique of collecting data through questionnaires (questionnaires) to distribute a list of closed questions. Data analysis used descriptive analysis is the analysis by detailing and explaining at length the relationship of research data that is typically provided in the form of tables and analysis based on the data in the table. The results showed the study showed that the characteristic variabel (X1) received an average score 4:37 which means very good. This shows that emloyess generally feel that they work according to their superior’s orders and according to their expertise. Of the distribution of questionnaires to the value of the variable (X2) working environment, safety statements work in companies closely related to employee performance improvement obtained average value of 4:21 means categorized very well from the distribution of questionnaires to the value of the variable (Y) the performance of the employee, the statement timeliness in completing work makes you happy to be categorized 4:03 excellent value